Experimental models for assessing treatments for spinal cord injury - Habgood, Mark (Henry Stewart Talks, 2011)
Development of neuro-protective therapies, Need for suitable experimental models, Low variance reproducible lesions, Spatio-temporal pattern of grey and white matter damage